PENDAMPINGAN MASYARAKAT TENTANG PAVING BLOK DI DESA KALIPAIT KECAMATAN TEGALDLIMO BANYUWANGI - DIMAS AJI PURNOMO; Harliwanti Prisilia; Heru Prasetyo; Ratih Nurhayati (Journal of Science and Social Development, 2022)
The road is an important community access that is used as mobilization. In most rural areas, the road conditions are still dirt, so there is a need to improve pavement, one of which is paving. Paving is a road pavement activity using paving blocks. Paving block is a building material composition made from a mixture of portland cement or other hydraulic adhesives, water and aggregate with or without other additives which do not reduce the quality of the concrete. This activity is carried out so that people understand and understand how to choose paving blocks and also how to install them in the field. The results of the community outreach were very enthusiastic as seen by the large number of attendees and also asking questions. Activities in the field of the community were given an explanation of how to arrange paving. This activity can also be used as a business opportunity for people who want to produce paving.